Case Report: Extracorporeal Membrane Oxygenation Followed by Intra-Aortic Balloon Counterpulsation Successfully Treated Cardiac Arrest Caused by Anomalous Origin of a Left Coronary Artery From the Right Coronary Sinus - Xu, Xiaolan; Xu, Peng; Wu, Xiaoyan; Lin, Hua; Chen, Yinhua; Hu, Xiaohua; Yu, Jiangquan; Zheng, Ruiqiang (Frontiers in Medicine, 2022)
Background: Anomalous origin of a coronary artery (AOCA) is defined as the failure of the coronary artery to originate from the normal coronary sinus. The anomalous origin of the left coronary artery arising from the right coronary sinus is rare, dangerous and at risk of malignant arrhythmia, sudden death, and high mortality. Case presentation: In this study, we present a 14-year-old adolescent male who went to a hospital with transient unconsciousness after exercise, who subsequently developed cardio arrest due to malignant arrhythmia. He was admitted to the intensive care unit, and who subsequently received successful veno-arterial extracorporeal membrane oxygenation-assisted circulation (VA ECMO) followed by intra-aortic balloon counterpulsation (IABP). Echocardiography and cardiac CTA were also performed, further confirming that the abnormal left coronary artery originated from the right coronary sinus. The patient subsequently underwent heart surgery. Conclusion: The successful treatment of the patient in this report was attributed to the immediately VA ECMO, supplemented by IABP. Establishing clear diagnosis is a process of multidisciplinary joint diagnosis, which provides a reference for clinicians when encountering similar cases.